Modified Immediate Sequential Bilateral Cataract Surgery (Clinical Cases) - I. B. Medvedev; D. F. Pokrovsky (Oftalʹmologiâ)
Purpose. Analysis of two clinical cases of immediate sequential bilateral cataract surgery according to the developed modified algorithm (mаISBCS).Materials and methods. The results of two clinical cases of mаISBCS are presented. In both cases, ultrasonic cataract phacoemulsification (FEC) was performed with implantation of an intraocular lens (IOL) under local anesthesia according to the standard technique through a corneal incision of 2.2–2.4 mm. IOL calculation was performed for emmetropic refraction. The modification (compared to the traditional one) of the technology of surgical intervention was based on the inclusion in the algorithm of a long (at least 60 minutes) break between operations for the purpose of a comprehensive ophthalmological examination with a further decision to perform an operation on the second eye.Results. In the first clinical case, the patient failed to measure the anterior-posterior axis by optical biometry before surgery. In such situations, the A-scan is used, which is considered less accurate due to human error and often leads to errors in the calculation of the IOL. In addition, a certain alertness was introduced by the fact of a significant (4 diopters) difference in the preoperative refraction of both eyes. Considering these provisions, after the first operation, after 60 minutes, the correctness of the IOL calculation was monitored by two methods — by measuring (optical biometrics) the anterior-posterior axis of the eye (APA, while the differences were less than 0.3 mm, which confirmed the A-scan data), as well as autorefractometry, which showed almost no deviation from the “target”. The presented results allowed us to formulate a decision to carry out the second operation. In the second clinical case, despite the absence of risk factors (optical biometrics was taken in two eyes, similar APA values), a postoperative refraction of +1.5 diopters was determined in the operated eye, which, apparently, is associated with the identified decrease (by 0.93 diopters) corneal curvature due to hydration of the corneal stroma in the area of surgical accesses and (or) changes in the tear film. The presented results allowed us to formulate a decision to postpone the second operation. At the same time, after a week, the restoration of the corneal tissue was noted, which was proved by the required (0.37 diopters) deviation of refraction from the target values.Conclusion. The use of mаISBCS technology provides the required clinical efficacy and can be recommended taking into account the epidemiological situation, especially for people with visually strenuous work.